Foreign Direct Investment and Regional Development : the Case of the Czech Republic - Hlaváček, Petr (Bezpośrednie inwestycje zagraniczne a rozwój regionalny na przykładzie Republiki Czeskiej, 2010)
The following text is focused on the analysis of direct foreign investments contribution for the regional development of the Czech Republic and individual regions especially Ústí nad Labem region. The higher risk of asymmetric development on the regional level lie in the higher concentration of foreign direct investments that are more dependent on the development of economic cycle. Ústí nad Labem region does not fall behind other regions when speaking about the incoming of direct foreign investments but it rather has weaker development in the net of research and development activities, innovative business and also worse education and labour structure of its inhabitants. Foreign investments of qualitative character, strengthening the competitiveness of individual regions of the Czech Republic, have therefore key role in further regional development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 110, s. 144-153